2013
DOI: 10.5194/bgd-10-16923-2013
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Neural network-based estimates of Southern Ocean net community production from in-situ O<sub>2</sub> / Ar and satellite observation: a methodological study

Abstract: Southern Ocean organic carbon export plays an important role in the global carbon cycle, yet its basin-scale climatology and variability are uncertain due to limited coverage of in situ observations. In this study, a neural network approach based on the self-organizing map (SOM) is adopted to construct weekly gridded (1° × 1°) maps of organic carbon export for the Southern Ocean from 1998 to 2009. The SOM is trained with in situ measurements of O2 / Ar-derived net community production (NCP) t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 122 publications
1
13
0
Order By: Relevance
“…Similarly, our NCP C algorithm yielded estimates of 23 mmol O 2 m −2 d −1 over the SeaWiFS time series for these months, though values from NCP D were lower (11 mmol O 2 m −2 d −1 ). Chang et al (2014), using a neural network approach, reported mean area-integrated NCP south of 50°S in the Southern Ocean of 18 mmol C m − 2 d −1 . For the SSTC region, they reported N30 mmol C m −2 d −1 , which is similar to our estimate of 33 mmol O 2 m − 2 d − 1 using NCP C (assuming PQ = 1.1), though this was double using NCP D , which may suggest that higher PQ values are more appropriate for this region.…”
Section: Validation Of Satellite Algorithms Of Net Community Productionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, our NCP C algorithm yielded estimates of 23 mmol O 2 m −2 d −1 over the SeaWiFS time series for these months, though values from NCP D were lower (11 mmol O 2 m −2 d −1 ). Chang et al (2014), using a neural network approach, reported mean area-integrated NCP south of 50°S in the Southern Ocean of 18 mmol C m − 2 d −1 . For the SSTC region, they reported N30 mmol C m −2 d −1 , which is similar to our estimate of 33 mmol O 2 m − 2 d − 1 using NCP C (assuming PQ = 1.1), though this was double using NCP D , which may suggest that higher PQ values are more appropriate for this region.…”
Section: Validation Of Satellite Algorithms Of Net Community Productionmentioning
confidence: 99%
“…Satellite models of NCP, based on net primary production and export, have also been proposed for the Southern Ocean (Nevison et al, 2012). Chang et al (2014) developed a neural network approach based on self-organizing maps to construct weekly gridded maps of organic carbon export for the Southern Ocean. The maps were trained with in situ measurements of O 2 /Ar to estimate NCP linked to potential predictors of NCP through statistical relationships with photosynthetically available radiation (PAR), Chla and mixed layer depth (MLD).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Kameyama et al [2013] found evidence for a strong positive relationship between DMS and net community production (NCP) in the North Pacific Ocean. Thus, it is possible that the DMS could be reconstructed by remotely derived NCP [Chang et al, 2014]. Thus, it is possible that the DMS could be reconstructed by remotely derived NCP [Chang et al, 2014].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Chang et al . [] and Li and Cassar [] recently estimated NCP for the Southern Ocean and the global oceans using in situ O 2 /Ar‐NCP estimates and various statistical methods including Artificial Neural Networks (ANNs), Support Vector Regression (SVR), and Genetic Programming (GP). Although these approaches estimate NCP relatively well, uncertainties remain significant, in part due to factors controlling NCP varying from one area to another.…”
Section: Introductionmentioning
confidence: 99%